Cellulose-Based Bio- and Nanocomposites: A Review - Kalia, Susheel; Dufresne, Alain; Cherian, Bibin Mathew; Kaith, B. S.; Avérous, Luc; Njuguna, James A. K.; Nassiopoulos, Elias (Cranfield University, 2011)
Cellulose macro- and nanofibers have gained increasing attention due to the high strength and stiffness, biodegradability and renewability, and their production and application in development of composites. Application of cellulose nanofibers for the development of composites is a relatively new research area. Cellulose macro- and nanofibers can be used as reinforcement in composite materials because of enhanced mechanical, thermal, and biodegradation properties of composites. Cellulose fibers are hydrophilic in nature, so it becomes necessary to increase their surface roughness for the development of composites with enhanced properties. In the present paper, we have reviewed the surface modification of cellulose fibers by various methods. Processing methods, properties, and various applications of nanocellulose and cellulosic composites are also discussed in this paper.